Masterclass. New First Certificate. Workbook. - Haines, Simon and Stewart, Barbara (Oxford Oxford University Press, 2003)
New First Certificate Masterclass is an effective exam preparation course for the revised Cambridge First Certificate in English (1996 revision). The course combines a systematic review of the language tested with extensive exam training.
Keywords: English Practice